ANALISIS PENGARUH CORPORATE IMAGE, VALUE, SERVICE QUALITY DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN PADA PT JAMSOSTEK (PERSERO) CABANG SEMARANG - Margiati, Maria Florensisca; Waluyo, Purwanto (Jurnal Ilmiah Telaah Manajemen, 2005)
This research in conducted to test model of corporate image, value, service quality and trust to Customer Satisfaction at PT Jamsostek (Persero) branch Semarang. Objectives of this study is examine the effect of corporate image, value, service quality, and trust to customer satisfaction. Data collected by using questionnaires is 313.The relationship between customer satisfaction and corporate image was tested by using Structural Equation Model (SEM) application of AMOS program provides evidences of one way causality between constructs, all with positive relations. Evidence support six out of ten hypotheses as statistically significance. The prominent finding of the study is that corporate image has significant positive effect through on service quality, value, trust and customer satisfaction. The findings of the study contribute to assurance’s management efforts in defining strategy to defend and or expanding their market shares in the getting harder competition. Several limitations of the study and suggestions for further research are also provide